Marketing turístico (2009)
ABSTRACT: Marketing is that one human activity directed to satisfy needs and desires by means of processes with interchange. The academic concept of Marketing would include the following fundamental ideas nowadays: - The direction of Marketing is a function of the companies including in its strategic planning. - The four fundamental activities for the development of the previous function turn around decisions on products, prices, communication and distribution. - The interchange does not underlie only in the goods and services, but any class of interchanges of values is included, which implies to extend the object of Marketing beyond the merely economic thing. - The satisfaction of desires and needs of the consumers must be placed therefore in the same level that the attainment of the objectives of the organizations.